2014
DOI: 10.1002/2013jb010485
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effective pressure law for permeability

Abstract: The permeability k of porous rocks is known to vary with confining pressure pc and pore fluid pressure pf. But it is, in principle, possible to replace the two‐variable function k(pf, pc) by a function k(peff) of a single variable, peff(pf, pc), called the effective pressure. Our goal in this paper is to establish an experimental method for determining a possibly nonlinear, effective pressure law (EPL) for permeability, i.e., find the function κs(pf, pc) such that the effective pressure is given by peff = pc −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
2
40
1
Order By: Relevance
“…Here, we have enough information to use equation . Li et al () estimated h / a ref for 22 sandstones from the same reservoirs investigated in the present paper, and found values very similar to those given in Table , even though they used a smaller reference pressure (20 MPa).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Here, we have enough information to use equation . Li et al () estimated h / a ref for 22 sandstones from the same reservoirs investigated in the present paper, and found values very similar to those given in Table , even though they used a smaller reference pressure (20 MPa).…”
Section: Discussionsupporting
confidence: 82%
“…Among our samples and those of Li et al (), we distinguished the ones reasonably consistent with the Walsh model from the others. The distinction is clearer in this study than in Li et al (), where most samples verified multiple models equally well. Data points consistent with the Walsh model tend to be located in the upper‐left quadrant of Figure , suggesting that microcracks and/or crack‐like pores may plausibly be considered to control the permeability of low‐porosity rocks (ϕ < 0.1) with pressure sensitivities γ higher than about 0.02 MPa −1 (yellow region).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Likewise, Li et al . [, ] and Bernabe [, ] also reported that there was a discrepancy in the coefficient caused by loading hysteresis and path.…”
Section: Experimental Backgroundmentioning
confidence: 99%